2022
DOI: 10.28918/religia.v25i1.4162
|View full text |Cite
|
Sign up to set email alerts
|

Tariqa Haq Naqsyabandi As a System of Islamic Iman Building in Pontianak, West Kalimantan

Abstract:  Tariqa (Eng.: Order; Tariqa) is known as an organization that only focuses on spiritual development. That is why Tariqa adherents are often trapped in rituals, which sometimes distance them from the outlined Islamic Iman. This study aims to determine the extent to which the Tariqa can become a system of Iman formation. This research was conducted in one of the largest Tariqas in Pontianak, namely the Tariqa Haq Naqsyabandi, which is headquartered at Perum IV Pontianak City. Based on the results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…He promoted to clean the students' heart and to always remember al-H} aqq (Allah). One of this t{ arîqa most prominent teaching was always reciting (sirr), even in the crowd (Gitosaroso et al 2022).…”
Section: The Rumi Centre: a Naqshbandî H{ Aqqânî Genealogymentioning
confidence: 99%
“…He promoted to clean the students' heart and to always remember al-H} aqq (Allah). One of this t{ arîqa most prominent teaching was always reciting (sirr), even in the crowd (Gitosaroso et al 2022).…”
Section: The Rumi Centre: a Naqshbandî H{ Aqqânî Genealogymentioning
confidence: 99%
“…Apart from using the Qur'an and Hadith approach, there are also Salawat studies using a Sufism approach, such as those conducted by Rofiatul Hosna (Hosna, 2018) and Muh. Gitosaroso (Gitosaroso et al, 2022). Both studies found that the recitation of Salawat is an implementation of Sufism values which then contributes to character building and strengthening faith in Allah and His Messenger.…”
mentioning
confidence: 97%